Impact of Awareness Campaign on Immunization Services in Southern Division Kabale Municipality. - Aharizira, Bridget (Kabale University, 2024)
This study examined the impact of awareness campaigns on immunization services in Southern Division, Kabale Municipality. The primary objective was to investigate how these campaigns influenced immunization services, with specific objectives to evaluate their role, identify challenges faced, and propose strategies for improvement. A descriptive research design with a qualitative approach was adopted, and data were collected using interviews, focus group discussions, and self-administered questionnaires from a sample of 80 participants, including residents, community leaders, and health workers. The study reviewed literature from 2013 to 2023 to provide a comprehensive analysis of previous and ongoing campaigns. The findings highlighted that awareness campaigns played a significant role in increasing public knowledge and utilization of immunization services. However, challenges such as limited community engagement, inadequate funding, and socioeconomic barriers hindered their effectiveness. The study recommended strategies to enhance campaign success, including fostering community involvement through collaborative workshops, leveraging local media for wider reach, and introducing feedback mechanisms to tailor messages to community needs. The research emphasized the importance of a multifaceted approach that integrates community participation, effective communication, and sufficient resources. By addressing the identified challenges and implementing these strategies, stakeholders could enhance immunization coverage and improve public health outcomes in Southern Division, Kabale Municipality.